Simultaneous Bilateral Knee Valgus Stress Radiographic Technique - Matheus Rocha de Aguiar, M.D.; Luiza B. Horta Barbosa, M.D.; Márcio B. Ferrari, M.D.; Nicholas I. Kennedy, M.D.; Jacqueline Vieira de Castro, P.T., Ph.D.; João L. Ellera Gomes, M.D., Ph.D. (Arthroscopy Techniques, 2017)
The medial collateral ligament is the most commonly injured knee ligament. Valgus stress radiographs are reported to be an effective way to quantify the medial compartment opening. However, most of the techniques require the presence of a physician in the radiograph room to apply a manual valgus stress force, and can only be performed in 1 knee at a time. These techniques, although extremely effective, increase radiation exposure to physicians, are time consuming, and require additional radiographs to compare the side-to-side difference. The purpose of this Technical Note is to describe our preferred valgus stress radiographic technique to evaluate medial side laxity, which offers several advantages compared with conventional manual techniques.